In Vivo EPR Characterization of Semi‐Synthetic [FeFe] Hydrogenases. Issue 10 (6th February 2018) - Mészáros, Lívia S.; Németh, Brigitta; Esmieu, Charlène; Ceccaldi, Pierre; Berggren, Gustav
Abstract: EPR spectroscopy reveals the formation of two different semi‐synthetic hydrogenases in vivo. [FeFe] hydrogenases are metalloenzymes that catalyze the interconversion of molecular hydrogen and protons. The reaction is catalyzed by the H‐cluster, consisting of a canonical iron–sulfur cluster and an organometallic [2Fe] subsite. It was recently shown that the enzyme can be reconstituted with synthetic cofactors mimicking the composition of the [2Fe] subsite, resulting in semi‐synthetic hydrogenases. Herein, we employ EPR spectroscopy to monitor the formation of two such semi‐synthetic enzymes in whole cells. The study provides the first spectroscopic characterization of semi‐synthetic hydrogenases in vivo, and the observation of two different oxidized states of the H‐cluster under intracellular conditions. Moreover, these findings underscore how synthetic chemistry can be a powerful tool for manipulation and examination of the hydrogenase enzyme under in vivo conditions. Abstract : A new tool for the in vivo examination of hydrogenase enzymes is presented. The insertion of synthetic cofactors into apo‐[FeFe] hydrogenase is monitored by EPR spectroscopy, revealing the successful formation of semi‐synthetic hydrogenases and providing insight into the Hox ‐state inside living cells.